Stunting socialization program as an effort to disseminate information - Nova Eka Winarti; Roski Apriliani; Hamzah Fathurrohman Arroja (Universitas Pendidikan Indonesia, 2024)
Stunting is a serious problem that is often found in toddlers and school-age children. One of the factors that influence this is parental knowledge about stunting. Stunting socialization is carried out as an effort to increase public understanding regarding nutritional intake, growth and development, prevention, and handling of stunting. This article aims to disseminate information related to stunting to the Bojong Village Community, Karangtengah District, Cianjur Regency. The implementation of socialization is delivered using the lecture method through direct presentations. Pamphlets were provided during the socialization to facilitate material delivery to participants. The results of the cmmunity services showed that there was enthusiasm from participants towards the socialization activities, which was marked by the many questions asked and the creation of active discussions between participants. The support of the local government was also a factor in the implementation of this socialization activity effectively. Abstrak Stunting merupakan masalah berat yang sering kali ditemui pada anak-anak usia balita dan usia masuk sekolah. Faktor yang mempengaruhi hal tersebut salah satunya pengetahuan orang tua mengenai stunting. Sosialisasi stunting dilakukan sebagai upaya untuk meningkatkan pemahaman masyarakat terkait asupan gizi, tumbuh kembang, pencegahan, dan penanganan stunting. Artikel ini bertujuan untuk mensosialisasikan informasi terkait stunting kepada Masyarakat Desa Bojong, Kecamatan Karangtengah, Kabupaten Cianjur. Pelaksanaan sosialisasi disampaikan dengan metode ceramah melalui presentasi secara langsung. Pemberian pamflet pada saat sosialisasi dilakukan untuk memudahkan penyampaian materi kepada peserta. Hasil pengabdian menunjukkan terdapat antusiasme peserta terhadap kegiatan sosialisasi yang ditandai dengan banyaknya pertanyaan yang diajukan, dan terciptanya diskusi aktif antar peserta. Dukungan pemerintah setempat juga menjadi faktor dalam terselenggaranya kegiatan sosialisasi ini secara efektif. Kata Kunci: Mahasiswa; Penyebab Stunting; Program Sosialisasi